Towards single electron transistor-based photon detection with microplasma-enabled graphene quantum dots. (6th October 2021) - Yeh, Pei-Chun; Ohkatsu, Genki; Toyama, Ryo; Tue, Phan Trong; Ostrikov, Kostya (Ken); Majima, Yutaka; Chiang, Wei-Hung
Abstract: Single-electron transistors (SETs) represent a new generation of electronic devices with high charge sensitivity, high switching speed, and low power consumption. Here a simple and controlled fabrication of graphene quantum dot (GQD)-based SETs for photon detectors has been demonstrated. The plasma-synthesized GQDs exhibit stable photoluminescence and are successfully used as the Coulomb islands between heteroepitaxial spherical-gold/platinum (HS-Au/Pt) nanogap electrodes. The as-fabricated GQD-SETs enable photon detection with 410 nm excitation owing to the ability of GQDs to generate photoluminescence emission.